1999
DOI: 10.1177/026988119901300204
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal patterns of antidepressant prescribing in primary care in the UK: comparison with treatment guidelines

Abstract: The objective of this study was to determine whether patients beginning therapy on the most common tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) differed in their likelihood of having antidepressant treatment that was consistent with recommended treatment guidelines in the UK. An analytical file constructed from a large general practitioner medical records database (DIN-LINK) from the UK for the years 1992-97 was constructed. A total of 16,204 patients with a new episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 25 publications
2
51
0
2
Order By: Relevance
“…It has been asserted in the mentioned study that 40% of patients with mood disorder (like depression) received no therapeutic intervention during a 12-month period. Another study in England has also emphasized on lower rate of antidepressants prescription in comparison to what has been suggested in their clinical guide [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has been asserted in the mentioned study that 40% of patients with mood disorder (like depression) received no therapeutic intervention during a 12-month period. Another study in England has also emphasized on lower rate of antidepressants prescription in comparison to what has been suggested in their clinical guide [10].…”
Section: Discussionmentioning
confidence: 99%
“…The time line of PAP use for any OSA/UARS patient may emerge in ways similar to the medical practice of attempting to increase the dosage of a drug while both early benefits and adverse effects occur at initial doses, a pattern common to antidepressant medications. 59 Since many patients demonstrate a capacity to endure a therapeutic process more gradually, it seems perplexing that so much emphasis has been placed on an arbitrarily devised adherence construct. Sleep medicine professionals are focused on encouraging greater PAP use and no doubt incorporate naturalistic approaches aligned with patients' learning curves, but adherence rules may interfere with this general practice model of care for select patients.…”
Section: Limitationsmentioning
confidence: 99%
“…Comorbid medical conditions generally are associated with poor adherence, 20 but findings on age and gender variations are mixed. 15,[20][21][22][23] Use of newer drugs [20][21][22]24 and mental health specialty services 15,16,20,21,25 generally have been associated with better antidepressant adherence. Economic status has rarely been included as an explanatory variable; we identified 1 study, which reported a positive association between income and adherence among veterans.…”
mentioning
confidence: 99%